1990
DOI: 10.3109/00016349009028706
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Myoma in Pregnancy

Abstract: A review was made of the medical records of 76 patients with uterine myomas during pregnancy with the aim of studying the time and method of diagnosis, symptomatology, treatment, and outcome of pregnancy. In 11 patients (15%) myomectomy was performed during pregnancy. The frequency of abortion was 18% in patients treated both conservatively and with myomectomy. Myomectomy during pregnancy is discouraged in the literature. In cases where conservative treatment cannot be practised it seems that the risk of spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 6 publications
1
33
0
1
Order By: Relevance
“…With respect to the distribution of myomas as a function of parity, Rice et al 17 reported that uterine myomas frequently develop in multiparas, but Gravind et al 18 noted that myomas are more prevalent in primiparas. In the study, uterine myomas were common in primi paras (40%).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the distribution of myomas as a function of parity, Rice et al 17 reported that uterine myomas frequently develop in multiparas, but Gravind et al 18 noted that myomas are more prevalent in primiparas. In the study, uterine myomas were common in primi paras (40%).…”
Section: Discussionmentioning
confidence: 99%
“…The mean blood loss was 280.0 B 83.6 ml. The mean and median number of myomas was 2.8 B 1.3 and 3 [1][2][3][4]. There were 2 corneous and 1 cystic degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators reported successful pregnancy outcomes after myomectomy during pregnancy [3,4,10]. Burton et al [6] performed surgical management of leiomyomata during pregnancy in 14 patients, a rate of 1.1 operations/10,000 births.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations